Mucoadhesive polymers-based film as a carrier system for sublingual delivery of glutathione. (10th October 2014) - Chen, Guanyu; Bunt, Craig; Wen, Jingyuan
Abstract: Objectives: The sublingual mucosa provides a promising route for the delivery of glutathione (GSH). However, challenges are encountered in developing sublingual mucoadhesive drug delivery formulations such as: prolonging drug retention, uniform drug content, desirable drug release profiles, adequate drug permeation and efficient delivery of GSH. The aim of this study was to develop a suitable mucoadhesive polymer-based sublingual film. Methods: The mucoadhesive films were prepared by casting method. Several characterization studies including thickness, weight uniformity, surface pH, elongation, mucoadhesiveness, swelling and erosion were carried out on preliminary formulations to optimise formulations for in-vitro drug release and ex-vivo permeation studies. Key findings: The optimal mucoadhesive polymer-based films showed acceptable physical properties and good mucoadhesion, and remained attached to excised porcine sublingual mucosa for sufficient time, providing a sustained delivery of GSH through the mucosal epithelial. Conclusion: The optimal mucoadhesive films may provide a promising drug delivery platform to develop commercial sublingual products of GSH as well as a wide range of protein and peptide drugs.